(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
Purpose(s): To highlight and differentiate the roles played by accounting expert witnesses and forensic accountants and to assess students’ perceptions of forensic accounting and forensic audit as an auxiliary tool in investigative practices of this economic and financial crime. This research is aimed at highlighting students’ knowledge in order to elucidate concepts that are often misunderstood due to the similarities they present. Method(s): Through descriptive research a general analysis of the role of forensic expertise and accounting in combating crime and assisting justice was conducted by collecting evidence of fraud and technical reports. Results: The answers showed there is confusion between the goals of accounting expert witnesses and forensic accountants and also highlighted the lack of specialized courses on the subject in favor of disseminating the culture in educational fields in Brazil. Contributions: Given the importance of both areas, comparative studies between the work of forensic accountants and accounting expert witnesses should be relevant in order to identify more efficient techniques to be used in combating and/or investigating accounting manipulations.